Organization In Islam As Worship - Dewi, Hana Maulida; Nuryani, Sella Ade (Pascasarjana STIE Miftahul Huda, 2024)
This study aims to examine the concept and implementation of organizations from an Islamic perspective. This study uses a literature study research method by analyzing various reference sources related to organizations in Islam. The results of the study indicate that organizations in Islam are not only viewed as formal structures, but also as a forum for achieving common goals that are in line with Islamic values. Islam views organizations as an important means of spreading religious teachings, improving the spiritual quality of members, and providing benefits to the wider community. Some examples of Islamic organizations discussed include mosques, Islamic educational institutions, zakat institutions, and da'wah organizations. This study provides an understanding of the importance of organizations as instruments in developing Muslims and realizing Islamic values in community life.